Towards Advances on Software Architecture Design of Constituents for Systems-of-Systems: Enabling Operational Independence - Teixeira, Paulo Gabriel; Graciano Neto, Valdemar Vicente (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2020: Anais Estendidos do XI Congresso Brasileiro de Software: Teoria e PráticaDO - 10.5753/cbsoft_estendido.2020.14602, 2020)
Over the years, knowledge on how to engineer software-intensive system-of-systems (SoS) have been expanded and advanced. However, challenges still remain. Constituent Systems (CSs) are required to instantaneously connect themselves to a SoS while still preserving their own operational independence. Moreover, SoS CS are subject to a sort of heterogeneities that makes it difficult to make decisions outside predefined frameworks, environment and hierarchical command-control structures. Hence, many of the systems currently available are not prepared to be part of an SoS, i.e., they can not maintain their operational independence despite their participation in one or more SoS. Based on this context, the main goal of this research is to exploit how to design a software architecture for systems that are intended to become part of a SoS in the future. To achieve this goal, we chose the urban mobility SoS domain, and then executed a software architecture design process to design a software architecture for an autonomous car as CS of this SoS. Later, we evaluated it through simulation. Preliminary results reveal that our proposal comply with the requirements raised during the architectural design process and can enable a system to be a constituent of a SoS while still preserving its operational independence.